Räuberbär - Kromhout, Rindert 1958- (Klopp, 1990)
Olaf liked to play robbers with his stuffed bear Diederik, but was told he was too old for such toys. He sold the bear at the flea market, but then felt sad.
Keywords: Flea markets -- Fiction; German language materials; Teddy bears -- Fiction